GE_GERICHTE P/7772/2020 vom 28. Juni 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VOL(DROIT PÉNAL);ABUS DE CONFIANCE;QUALITÉ POUR AGIR ET RECOURIR | CPP.310; CP.319; CP.158; CPP.385; CPP.115; CPP.118